The Great Exhibition, 1851 : a sourcebook - Shears, Jonathon; Shears, Jonathon (Interventions, 2017)
This is the first anthology of its kind. It presents a comprehensive array of carefully selected primary documents, sourced from the period before, during and after the Exhibition in Hyde Park in 1851. Drawing on contemporary newspapers and periodicals, the archives of the Royal Commission, diaries, journals, celebratory poems and essays, many of these documents are reproduced in their entirety, and in the same place, for the first time. The book provides an unparalleled resource for teachers and students of the Exhibition and a starting point for researchers new to the subject. Subdivided into six chapters - Origins and organisation, Display, Nation, empire and ethnicity, Gender, Class and Afterlives - it represents the current scholarly debates about the Exhibition, orientating readers with helpful, critically informed, introductions. What was the Great Exhibition and what did it mean?